2011
DOI: 10.1080/08870446.2011.626856
|View full text |Cite
|
Sign up to set email alerts
|

Heart attack risk perception biases among hypertension patients: The role of educational level and worry

Abstract: Risk biases such as comparative optimism (thinking one is better off than similar others) and risk inaccuracy (misestimating one's risk compared to one's calculated risk) for health outcomes are common. Little research has investigated racial or socioeconomic differences in these risk biases. Results from a survey of individuals with poorly controlled hypertension (N=813) indicated that participants showed (1) comparative optimism for heart attack risk by underestimating their heart attack risk compared to sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Some of the educational inequalities in AMI incidence might also be explained by differences in health awareness,[41], [42] psychosocial factors[43], [44] or differences in compliance to treatment and adherence to advices on change of lifestyle [45]…”
Section: Discussionmentioning
confidence: 99%
“…Some of the educational inequalities in AMI incidence might also be explained by differences in health awareness,[41], [42] psychosocial factors[43], [44] or differences in compliance to treatment and adherence to advices on change of lifestyle [45]…”
Section: Discussionmentioning
confidence: 99%
“…For analysis, this response was dichotomized into (yes/no) “Agree/Strongly agree” versus “Disagree/Strongly disagree” that I am less likely to get diabetes. To assess perceived comparative risk of heart attack, participants were asked: “Compared to other people your age, how likely do you think it is that you could have a heart attack in your lifetime?” [20,21]. Participants could rate the likelihood of having a heart attack in their lifetime by selecting a number from 1 to 5, with 1 = much less likely, 3 = about the same risk, and 5 = much more likely.…”
Section: Methodsmentioning
confidence: 99%
“…acknowledge the lack of work on income and education and optimistic bias. Their study on patients with hypertension found a significant effect from education (more education, more bias) but only equivocal findings from income . Income was found to be a predictor of the related phenomenon of unrealistic optimism .…”
Section: Introductionmentioning
confidence: 95%